Mechanism and applications of lithium amide-induced asymmetric rearrangements of 4-substituted and 4,4-disubstituted cyclopentene oxides to cyclopentenols - Hodgson, D; Gibbs, A; Drew, M (1999)
The preparation and lithium amide-induced rearrangements of 1,2-dideuterated 4-substituted cyclopentene oxides 11 and 19 are described, providing insight into the deprotonation mechanisms operating in such systems. Highly enantioselective syntheses of 4-substituted cis-4-hydroxymethylcyclopent-2-en-1-ols 32a-c are described. Also described are asymmetric syntheses of prostaglandin precursor 40 and (+)-iridomyrmecin (48) via highly enantioselective rearrangement of the epoxide 3 and subsequent Ireland-Claisen rearrangement. © The Royal Society of Chemistry 1999.